Isolation and identification of the Serratia marcescens causing septicemia in the silkworms from Yen Bai province and prevention measures - Hanh, Nguyen Thuy; Ngoc, Pham Minh; Tuan, Hoang Minh (Vietnam Journal of Biotechnology, 2024)
In Yen Bai (Northern Viet Nam), sericulture is an important part of agriculture. However, bacterial diseases often cause severe economic loss in sericulture. The results of this research are the first to use a combination of biochemical identification methods and sequencing of the 16S rRNA gene region to diagnose and determine the origin of the pathogen causing septicemia in silkworms collected from Yen Bai province. From the collected silkworm samples with septicemia, a strain of Serratia marcescens bacteria was isolated with morphological characteristics, and typical basic biochemical test. Additionally, the 16S rRNA gene region of the bacterial strain S. marcescens was sequenced. Research results showed that the MD2-16-27F bacterial strain has 99.63% similarity with the S. marcescens strain JW-CZ2. Research on preventing this bacterium shows that the disinfection solution, which contains the active ingredients of trichloroisocyanuric acid (0.0008 mol), formaldehyde (0.0059 mol), calcium hypochloride (0.0031 mol) and alcohol (0.137 mol), effectively prevented the growth of this bacterium after exposed to it for 30 minutes at a temperature of 24-25oC. Antibiotic active ingredients, Norfloxacin (10 μg/l) and Doxycycline (30 μg/l), were effective in preventing S. marcescens bacterium with high sensitivity level; the antibacterial ring diameter of Doxycycline was 31 mm and that of Norfloxacin was 25 mm. The results of this study can be applied to the general prevention of septicemia in silkworms caused by S. marcescens bacteria in the Northern part of Vietnam, particularly in Yen Bai in particular and the North of our country in general.